Regarding brick work, approval of the brick sample & rate analysis of the brick work using Mirpur ceramic bricks - Brac University (Brac University, 2023)
This record consists of general correspondence regarding brick work, approval of the brick sample & rate analysis of the brick work using Mirpur ceramic bricks for BRAC University new campus project.